The Effect of Perception of Ease and Service Features Upon Interest in Using Mobile Banking on BCA Mobile Application at BCA Bandung Regional - Wala Erpurini; Devi Silaen; Tiara Nurhasanah; Nur Alamsyah (Indonesian Journal of Business Analytics, 2023)
The goal of this research is to examine the effect of perception of ease and service features on the intention to use mobile banking partially or simultaneously on the BCA Mobile application. This research was conducted with BCA customers at the BCA Bandung regional office who utilized the BCA Mobile application for Mobile Banking. In this research, a quantitative method with a descriptive and associative approach was utilized. Individuals, namely BCA customers in the BCA Bandung regional office who utilize BCA Mobile, serve as the unit of analysis for this research. The sample size for this research is one hundred respondents. The sampling method based on sampling incidental, yet adheres to predefined criteria. The analytical approach employs multiple linear regression analysis, hypothesis testing, and the coefficient of determination, in addition to verifying the instrument's validity and reliability. Results indicated that perception of ease and service features influenced the intention to use Mobile Banking on the BCA Mobile application, either partially or concurrently. To facilitate client transactions, it is planned that Bank BCA would include new technologies and interactive service elements into the BCA Mobile application.